Confirmation as a genre of religious discourse (on the material of ego-documents of Lutherans of the Brunnenthal colony XIX-XX cc.) - Shindel', Svetlana Vladimirovna; Maslova, Antonina Nikolaevna; Kosheleva, Ol'ga Nikolaevna (Филология: научные исследования, 2025)
The article is devoted to the Povolzhie Germans' confessional ego documents. The subject of the study are linguistic and extra linguistic markers of religious genre considering the examples of confirmation certificates of Lutherans lived in Brunnental settlement. Confirmations in the form of written certificates contain quotes from the Bible, fragments of preaching, lines of hymns, and choral verses in the German language. Extra linguistic markets include graphic images of plots of Bible stories, the image of the Savior, Gothic fractures, peculiarities of artistic design (floral components and predominance of red colour), fragments of musical spiritual culture. The set of linguistic and extra linguistic markers organizes specific distinct structure in the form of value prescriptions for a Lutheran. Comparative method made it possible to classify ego documents samples. Semiotic, lingo cultural methods contributed to identification of religious discourse. The scientific novelty lies in a complex character of examination of samples of confessional ego documents of Lutherans lived in Brunnental settlement from the point of view of their genre specifics. The relevance of the work is due to the need to study the uniqueness of religious discourse on the basis of authentic written certificates remained. The totality of identified linguistic and extra linguistic markers allows us to attribute confirmation certificates to a secondary genre of religious discourse in Protestantism. The theoretical significance of the study is in the fact that the given work contributes to the development of the theory of discourse, characterizing one of its types, namely religious discourse. The result of the study may be used at lectures and seminars on the subject "Theory of language" ang may interest those who study German confessional lingo culture.